2019
DOI: 10.3390/ijerph16234685
|View full text |Cite
|
Sign up to set email alerts
|

Encounter with Bullying in Sport and Its Consequences for Youth: Amateur Athletes’ Approach

Abstract: In recent years, the problem of bullying, existing in sport and arising in athletes’ relationships, is increasingly emphasized. The aim of this research was to reveal the specificity of bullying in athletes’ interrelationships by elaborating on causes of its emergence, nature of actions, and its consequences. To achieve the research aim, a qualitative research paradigm was chosen. The theoretical part of the research was prepared by applying the methods of scientific literature analysis and analogy. The empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…The interviewees commented on the fear of reliving those situations, the difficulties of establishing social relationships and the changes that had taken place in their personalities. As opposed to the study by Vveinhardt et al (2019a), the victims did not show "positive" consequences of the situation in the long term (being bullied does not make the victim "stronger"), but stated that the experience had fostered a strong sense of empathy toward situations of bullying that may occur in their environment. Moreover, although victimization in the school setting may facilitate substance abuse behaviors (Moore et al, 2017) in our study it was not mentioned by any of the participants, probably due to the fact that people who spend more time practicing sport have a lower frequency of consumption (Schmidt et al, 2019).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The interviewees commented on the fear of reliving those situations, the difficulties of establishing social relationships and the changes that had taken place in their personalities. As opposed to the study by Vveinhardt et al (2019a), the victims did not show "positive" consequences of the situation in the long term (being bullied does not make the victim "stronger"), but stated that the experience had fostered a strong sense of empathy toward situations of bullying that may occur in their environment. Moreover, although victimization in the school setting may facilitate substance abuse behaviors (Moore et al, 2017) in our study it was not mentioned by any of the participants, probably due to the fact that people who spend more time practicing sport have a lower frequency of consumption (Schmidt et al, 2019).…”
Section: Discussioncontrasting
confidence: 66%
“…However, there has been little research looking at bullying situations among the victims themselves. Jewett et al (2019) analyzed the negative emotional consequences of being a victim and Vveinhardt et al (2019a) focuses on its nature, causes and consequences. Given the absence of research analyzing the phenomenon of bullying in sport in depth from the perspective of the victims themselves during childhood and/or adolescence, the purpose of this research was to determine retrospectively the experiences of bullying among athletes who had been victimized during their youth sport training.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying in sports and in physical education classes mostly occurs in locker rooms and playing areas (Mishna et al, 2019). Locker rooms are typically small spaces that provide ample opportunity for social interaction before or after training, normally without adult supervision (Kerr et al, 2016;Nery et al, 2020;Vveinhardt et al, 2019a). Insults and homophobic comments are common here, particularly among boys, and are often considered part of the norm (Iida & McGivern, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Insults and homophobic comments are common here, particularly among boys, and are often considered part of the norm (Iida & McGivern, 2014). This, combined with the effects of peer pressure, can impose a code of silence ("what happens in the locker room stays in the locker room"), meaning coaches may often be unaware that bullying is taking place (Prat et al, 2020;Vveinhardt et al, 2019a). Victims of bullying generally try to cope on their own and rarely turn to others (e.g., teammates, family members, or coaches) for help (Collot & Dudink, 2010;Nery et al, 2019;Vveinhardt et al, 2017); the main emotions reported were anger and sadness.…”
Section: Discussionmentioning
confidence: 99%
“…First, by reproducing relational violence over time, a pattern of victimization is maintained and can become a profile established and settled in young people that continues into adulthood. Therefore, it has consequences not only in their personal, family, and social spheres but also in the workplace [131][132][133][134][135][136][137][138]. We call this phenomenon "the spiral of relational violence" in university students.…”
Section: Discussionmentioning
confidence: 99%